2016
DOI: 10.1016/j.apenergy.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pelletization and torrefaction depots: Optimization of depot capacity and biomass moisture to determine the minimum production cost

Abstract: In the present study, the biomass upgrading depot capacity and biomass feedstock moisture were optimized to obtain the minimum production cost at the depot gate for the production of woody biofuels. Three technology scenarios are considered in this study: 1) conventional pellets (CP), 2) modestly torrefied pellets (TP1) and severely torrefied pellets (TP2). TP1 has the lowest cost of $7.03 /GJ LHV at a moisture of 33 wt.% and a depot size of 84 MW LHV. The effects of climatic conditions and biomass field condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The sizing of the depots is based on a resource approach that determines the available supply of corn stover in the territory. The assumptions of depots’ size in this study are smaller than those in the literature because of the pedoclimatic conditions, the dispersion of the feedstock in the territory, and the low participation rate of farmers. To select the sizing of the biomass depots, Eqn (3) is used (adapted from Ministry of Natural Resources of Quebec) to estimate the potential tonnage of corn stover technically and ecologically available in southern Quebec: CSa=A*LR*Y*WR*RR*italicARwhere CS a is the potential corn stover technically and ecologically available annually in the research area (DMg); A is the potential harvested corn lands area, set to ~200 k ha (120 km radius); LR is the ratio of corn lands in Quebec that can tolerate material removal, set to 50% authors’ assumption based on literature; Y is the grain yield, average 2015–2017, set to 10.2 Mg ha −1 (163 bu ac −1 ) (15% moisture content); WR is the residue‐to‐grain weight ratio, set to 66% authors’ assumption based on the land yield and the culture condition; RR is the stover removal ratio, set to 25% based on the soil quality and yield; and AR is the annual biomass availability rates (farmers’ participation rate), set to 10–40% authors’ assumption based on literature…”
Section: Case Studymentioning
confidence: 91%
See 1 more Smart Citation
“…The sizing of the depots is based on a resource approach that determines the available supply of corn stover in the territory. The assumptions of depots’ size in this study are smaller than those in the literature because of the pedoclimatic conditions, the dispersion of the feedstock in the territory, and the low participation rate of farmers. To select the sizing of the biomass depots, Eqn (3) is used (adapted from Ministry of Natural Resources of Quebec) to estimate the potential tonnage of corn stover technically and ecologically available in southern Quebec: CSa=A*LR*Y*WR*RR*italicARwhere CS a is the potential corn stover technically and ecologically available annually in the research area (DMg); A is the potential harvested corn lands area, set to ~200 k ha (120 km radius); LR is the ratio of corn lands in Quebec that can tolerate material removal, set to 50% authors’ assumption based on literature; Y is the grain yield, average 2015–2017, set to 10.2 Mg ha −1 (163 bu ac −1 ) (15% moisture content); WR is the residue‐to‐grain weight ratio, set to 66% authors’ assumption based on the land yield and the culture condition; RR is the stover removal ratio, set to 25% based on the soil quality and yield; and AR is the annual biomass availability rates (farmers’ participation rate), set to 10–40% authors’ assumption based on literature…”
Section: Case Studymentioning
confidence: 91%
“…In this industry, there is no clear rule of economies of scale. A larger biorefinery implies a larger supply radius, which increases the transport cost of a low‐density biomass …”
Section: Centralized Versus Decentralized Configurationmentioning
confidence: 99%
“…They analyzed the effects under three conditions 1) Balanced market, under oligopolistic-oligopsonistic equilibrium pricing 2) Bio-refineries maintain a supply region, based on average yield density 3) Bio-refineries maintain a supply region, based on "Derisked" yield density. Chai and Saffron (2016) considered 3 scenarios with regard to storage capacity and the amount of biomass moisture content in order to produce woody biomass-based biofuel. Their model minimizes the costs and determines the amount of moisture and biomass optimal warehouse size.…”
Section: Other Methodsmentioning
confidence: 99%
“…Lamers et al (2015) suggested the benefits from incorporating biomass processing facilities (biomass depots) into the overall feedstock supply chain outweigh the costs and should be aggressively pursued. Chai and Saffron (2016) reviewed optimal capacity for pellet and torrefied wood depot facilities highlighting the dependence of moisture (drying energy) with optimal depot ranges between 60-100 MW [450,000-815,000 bdmt yr -1 (500,000-900,000 bdt yr -1 ) of feedstock] while others have suggested 63,000-135,000 bdmt yr -1 (70,000-150,000 bdt yr -1 ) may be optimal for fixed placement pellet depots (Sultana et al, 2010).…”
mentioning
confidence: 99%
“…Studies have typically not looked at a wide range of regional variations in supply chain costs of mobile systems, though portions of the biomass supply chain have been studied including trucking capacities and supply implications Jacobson et al, 2016). The study of transportable facility design to produce higher value wood products (biochar, torrefied wood, briquettes, pellets) is less studied (Chai and Saffron, 2016;Berry and Sessions, 2018a, b). Berry and Sessions (2018a) take this concept a step further by optimizing strictly transportable facilities [13,,000 bdmt yr -1 (15,000-50,000 bdt yr -1 )] for a biochar facility finding optimal time between moves being 1 to 2.5 years.…”
mentioning
confidence: 99%